3
$\begingroup$

Let $x_1$,$x_2$,$x_3$ be the roots of the cubic $x^3+px+q$ over $\mathbb Q$, the idea is that rational solutions $(u,v)$ of the equation

$$(u-x_1)^{1/3}+ (u-x_2)^{1/3}+ (u-x_3)^{1/3} = {v}^{1/3} \quad (1)$$

actually lie on a certain affine plane algebraic curve, which can be constructed as follows. First, consider the variety $V$ in the afiine space $\mathbb A^8\langle u,v,x_1,x_2,x_3,y_1,y_2,y_3\rangle$ over the function field $\mathbb Q(p,q)$, $$V: \left\{ \begin{aligned} &x_1+x_2+x_3=0 , \\ &x_1 x_2 + x_2 x_3+x_1 x_3 =p,\\ &x_1 x_2 x_3 =-q, \\ &y_1^3= u-x_1,\\ &y_2^3= u-x_2,\\ &y_3^3= u-x_3,\\ & (y_1 +y_2 +y_3 )^3 = v .\\ \end{aligned} \right. $$

Next, define our curve $C$ as the image of $V$ under the map $$ f : V \to \mathbb A^2 \langle x,y \rangle,$$ $$(u,v,x_1,x_2,x_3,y_1,y_2,y_3) \mapsto (u,v).$$ Finally, get a polynomial defining $C$ with the aid of Magma Calculator:

> F<p,q>:=FunctionField(Rationals(),2);
> A8<x1,x2,x3,y1,y2,y3,u,v>:=AffineSpace(F,8);
> V:=Scheme(A8,[x1+x2+x3, x1*x2+x2*x3+x3*x1-p, x1*x2*x3+q,
> u-x1-y1^3, u-x2-y2^3, u-x3-y3^3, (y1+y2+y3)^3-v]);
> A2<x,y>:=AffineSpace(F,2);
> f:=map<V->A2|[u,v]>;
> C:=Image(f); C;
Scheme over Multivariate rational function field of rank 2 over Rational Field
defined by
x^7*y^2 - 1/27*x^6*y^3 + 1/9*x^5*y^4 + 11/9*p*x^5*y^2 - q*x^5*y - 1/243*x^4*y^5
    - 13/27*p*x^4*y^3 + 11/9*q*x^4*y^2 + 2/9*p^2*x^4*y + 1/243*x^3*y^6 +
    46/243*p*x^3*y^4 - 16/27*q*x^3*y^3 + 7/27*p^2*x^3*y^2 - 5/9*p*q*x^3*y -
    1/27*p^3*x^3 - 1/6561*x^2*y^7 - 10/729*p*x^2*y^5 - 8/243*q*x^2*y^4 -
    73/243*p^2*x^2*y^3 + 26/27*p*q*x^2*y^2 + (1/9*p^3 - 7/9*q^2)*x^2*y -
    1/9*p^2*q*x^2 + 1/19683*x*y^8 + 35/6561*p*x*y^6 - 7/729*q*x*y^5 +
    29/243*p^2*x*y^4 - 155/243*p*q*x*y^3 + (-1/9*p^3 + 19/27*q^2)*x*y^2 +
    2/9*p^2*q*x*y - 1/9*p*q^2*x - 1/531441*y^9 + 1/6561*p*y^7 + 53/6561*q*y^6 -
    1/243*p^2*y^5 + 20/243*p*q*y^4 + (1/27*p^3 - 28/243*q^2)*y^3 - 1/9*p^2*q*y^2
    + 1/9*p*q^2*y - 1/27*q^3

Note. The bijection between rational solutions $(u,v)$ of equation $(1)$ and rational points $(x,y)$ on the curve $C$ is straightforward: $(u,v) \longleftrightarrow (x,y)$.

Futher, by using formulas in this answer, one can build a rational map (which will be denoted by $\varphi$) from the elliptic curve $E: e^2=d^3+27p^3+\frac{729}4q^2$ to the curve $C$:

> A<d,e>:=AffineSpace(F,2);
> E := Curve(A,[-e^2+d^3+27*p^3+(729/4)*q^2]); 
> u:=(1/9*d^6*e - 27/2*q*d^6 - p*d^5*e - 243/2*p*q*d^5 + (-12*p^3 -
>     81*q^2)*d^3*e + (-1458*p^3*q - 19683/2*q^3)*d^3 + (216*p^4 +
>     1458*p*q^2)*d^2*e + (-2592*p^6 - 34992*p^3*q^2 - 118098*q^4)*e)/(d^7
>     + 9*p*d^6 + 81*p^2*d^5 + (216*p^3 + 1458*q^2)*d^4 + (972*p^4 +
>     6561*p*q^2)*d^3 + (11664*p^6 + 157464*p^3*q^2 + 531441*q^4)*d);
> w:=(1/9*d^6*e + 27/2*q*d^6 + 2*p*d^5*e + (-12*p^3 - 81*q^2)*d^3*e +
>     (1458*p^3*q + 19683/2*q^3)*d^3 + (-432*p^4 - 2916*p*q^2)*d^2*e +
>     (-2592*p^6 - 34992*p^3*q^2 - 118098*q^4)*e)/(d^7
>     + 9*p*d^6 + 81*p^2*d^5 + (216*p^3 + 1458*q^2)*d^4 + (972*p^4 +
>     6561*p*q^2)*d^3 + (11664*p^6 + 157464*p^3*q^2 + 531441*q^4)*d);
> m:= e*( d^5 + 12*p*d^4 + 54*p^2*d^3 + (108*p^3 + 729*q^2)*d^2 + 
> (-648*p^4 -    4374*p*q^2)*d) +
>     81/2*q*d^5 + (4374*p^3*q + 59049/2*q^3)*d^2;
> n:=d^6 + 9*p*d^5 + 81*p^2*d^4 +
>     (216*p^3 + 1458*q^2)*d^3 + (972*p^4 + 6561*p*q^2)*d^2 + 
> (11664*p^6 +    157464*p^3*q^2 + 531441*q^4);
> phi:=map<E-> C | [u, 3*u+3*m/n-3*w]>;  
> time Image(phi) eq C;
true
Time: 66.680

If we pick the point $P:=(-3p,\frac{27}2 q)$ on $E$, it can be verified that the preimage of the point $\varphi(nP) \in C$ has cardinality $1$ for all $n\in \mathbb Z$ such that $|n|<5$. It thus seems plausible that the map $\varphi : E \to C $ is in fact a birational isomorphism.

Question 1. Is it possible to find the inverse of the map $\varphi$?

Question 2. How can we transform the curve $C$ into Weierstrass normal form without knowing about $E$ in advance?

$\endgroup$
0
$\begingroup$

$x^3+px+q=0$ ------$(1)$

$(u-x_1)^{1/3}+ (u-x_2)^{1/3}+ (u-x_3)^{1/3} = {v}^{1/3} \quad (2)$

For, $(p,q)=(-7,6)$ equation $(1)$ has roots $(x_1,x_2,x_3)=(-3,2,1)$

And equation $(2)$ has solution $(u,v)=(-1,-3)$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.